Pengembangan Bahan Pembelajaran Berbasis Hypercontent pada Pembelajaran Tematik di Sekolah SMP Negeri 13 Makassar - Alfianto Alfianto; Heri Heri (Jurnal Kajian dan Penelitian Umum, 2024)
This research aims to develop hypercontent-based learning materials for thematic learning at SMP Negeri 13 Makassar. The development method used is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The analysis stage is carried out to identify learning needs and student characteristics. The design stage includes planning the hypercontent structure and graphic design. The development stage includes creating content and learning media. Implementation was carried out through limited trials on selected groups of students. Evaluation is carried out to measure the effectiveness of learning materials developed based on student responses and learning performance. The research results show that hypercontent-based learning materials can increase students' interest and understanding of thematic learning materials. The implication of this research is the importance of applying technology in developing learning materials to facilitate interactive and interesting learning for students in this digital era.